Study of The Interaction of UV Photografting on The Poly(Ethylene Terephthalate) (PET) in its Application as Food Packaging - Nur Aini Fauziyah; Primasari Cahya Wardhani; Pardi Sampe Tola; Nailul Hasan; Dira Ernawati (Future Science, 2023)
This review article focused on the investigation of UV radiation's interactions with PET plastic in photografting. The photografting technique involved exposing PET packaging to UV radiation before utilizing it to package food. Surface graft polymerization was frequently carried out using UV light, frequently in the presence of a photoinitiator or photosensitizer. The results were intriguing since UV irradiation caused by PET and UV interaction will result in a hydrophilic nature in order for surface photography to create photografting and PET film with antibacterial properties. Therefore, many other industries, including the food industry, use photografting in this way.